Protection induced by cholecystokinin-8 (CCK-8) in ethanol-induced gastric lesions is mediated via vagal capsaicin-sensitive fibres and CCKA receptors. - Evangelista, S. (1991)
We have investigated the effect of intravenous injection of cholecystokinin-8 (CCK-8) and other peptides on gastric lesion formation in response to an intragastric perfusion with 25% ethanol in rats anaesthetized with urethane. 2. Intravenous injection of CCK-8 (50-100 nmol kg-1), but not bombesin (1-100 nmol kg-1), calcitonin gene-related peptide (1-50 nmol kg-1), neurokinin A (1 mumol kg-1) or substance P (100 nmol kg-1), induced protection against gastric haemorrhagic lesions produced by ethanol. 3. The CCKA-antagonist L-364,718 (2.45 mumol kg-1, i.v.) increased the lesion index induced by ethanol and reversed the protective effect of CCK-8 (50 nmol kg-1, i.v.). The CCKB-antagonist L-365,260 (5 mumol kg-1, i.v.) and a lower dose of L-364,718 (0.25 mumol kg-1, i.v.) were ineffective. 4. The gastric protective effects afforded by CCK-8 (50 nmol kg-1, i.v.) were not observed in vagotomized-rats and were reduced by capsaicin pretreatment. In capsaicin-pretreated rats there was a worsening of gastric lesions induced by ethanol-perfusion as compared to those observed in vehicle-pretreated rats. 5. These results demonstrate that the mucosal protective effect of CCK-8 involves, at least in part, the activation of CCKA-receptors and is mediated by vagal capsaicin-sensitive fibres.